Distinct Upward Propagation of the Westerly QBO in Winter 2015/16 and Its Relationship With Brewer-Dobson Circulation - Kang, Min-Jee; Son, Seok-Woo; Chun, Hye-Yeong (Geophysical Research Letters, 2022)
A westerly phase of the quasi-biennial oscillation (QBO) was disrupted in 2015/16. Previous studies have primarily focused on the cause of the localized negative momentum forcing, initiating the QBO disruption. However, the upward displacement of the westerly QBO followed by the negative momentum forcing, clearly observed in 2015/16, has received less attention. This study shows that the distinct upward propagation of the westerly winds during the 2015/16 QBO disruption was contributed by the strong Brewer-Dobson circulation (BDC). Strong Rossby waves with wavenumber 1 propagating from the troposphere mainly drove the strong BDC. Potential contributions of El Nino and Barents-Kara sea ice reduction to Rossby waves are also discussed. Y 1